Analisis Kesiapan Guru Dalam Perencanaan Pembelajaran Berdiferensiasi (Implementasi Kurikulum Merdeka Di MTSN 4 Demak) - Sukarman, Sukarman; Manasikana, Arina (Lembaga Kajian dan Penerapan Nilai - Nilai Islam Unissula, 2023)
This research aims to describe the readiness of Islamic religious education teachers, to describe the difficulties experienced by teachers, and to describe the supporting and inhibiting factors for implementing the independent learning curriculum at Madrasah Tsanawiyah Negeri 4 Demak. This research uses a qualitative approach. The type of research is descriptive qualitative. The research location is Madrasah Tsanawiyah Negeri 4 Demak, with primary data sources being the principal, PAI teachers at MTsN 4 Demak, and using secondary data in the form of profiles of MTsN 4 Demak. Data analysis techniques include data redaction, data presentation, and verification. The results of the research are 1) The readiness of Islamic religious education teachers in preparing teaching modules and project modules for strengthening the profile of Pancasila students. 2) Teacher readiness in implementing differentiated and student-centered learning at MTsN 4 Demak, teachers’ lack of knowledge regarding differentiated learning makes teachers less than optimal in differentiated and student-centered learning, teachers only differentiate according to what they see when learning takes place, The lack of direct handling of students makes differentiated learning less than optimal. 3) Teacher readiness in carrying out formative and summative assessments for extracurricular projects to strengthen the profile of Pancasila students at MTsN 4 Demak, regarding formative and summative assessment, the readiness is not optimal because most teachers do not know how and what the assessment looks like, related to intra-curricular activities and the project to strengthen the profile of Pancasila students several activities entrepreneurship work from agricultural products).